O PERFIL SÓCIOECONÔMICO E EDUCACIONAL DO EGRESSO DA PENITENCIÁRIA INDUSTRIAL DE GUARAPUAVA QUE OPTOU EM REMIR PENA PELA EDUCAÇÃO - Gaertner, Daniel Tille (2013)
The present study has as objective to research the notion of remission through the study and as the general objective, we tried to evidence the profile for the egress from the Industrial Penitentiary in Guarapuava – (Penitenciária Industrial de Guarapuava - PIG), which opted for reducing the sentence through education, socioeconomic and educational situation, having as time framework those who egressed from January 2010 to December 2011. The purpose of the research, therefore, was to demonstrate the profile of 54 men who served the sentence at PIG and benefited withthe remission through the study, which was a result of a clash of data obtained from the documents of Pro-egress Program in Guarapuava, CEEBJA Nova Visão and PIG. It is essentially a descriptive and bibliographic study. The current work was divided into three chapters. In the first, we tried to clarify the figure of the State, its relation with Law, its evolution together with criminal law, its sentences and its purposes, as well as how it focuses on the existing relation between the State and the power to punish, where it was established the existence of so called “enemies”. Also, at the moment, as well as along the research, criticisms toward the state and the capitalism were presented, which ended up influencing sentences evolution and aided in the origin of penitentiaries. The second chapter deals with the institution of remission, its modalities and, mainly focused on the remission through the studies, carrying out a critical analysis on its actual purposes. Finally, in the third chapter, it was evidenced the socioeconomic profile and the schooling level of the egressed individual from the Industrial Penitentiary inGuarapuava, which remitted sentences through the studies, characterizing then the Industrial PenitentiaryinGuarapuava, the educational system provided in the location as well as the experience in the court of criminal enforcement in Guarapuava. The theoretical contribution was based on official documents and on scientific production of intellectuals and researchers, standing out Bitencourt, Baratta, Leal, Guimarães, Costa, Paduanni, among others. It was evidenced that the egress from PIG, despite serving service in an establishment which follows the law, does not have a profile that distinguishes it from the standard in the state of Paraná. Moreover, we verified that PIG cannot be considered as exemplary, but as acountertrend.